Assessment of fertilization, hatching and survival rates of cold-shock induced triploid purebred African Catfish, Clarias gariepinus x Clarias gariepinus. - Mercano, Mary Louise Villar
Originally introduced in Vietnam, Clarias gariepinus is rapidly gaining widespread importance worldwide. It is the only introduced species that has significant impact on Asian aquaculture industry. Though it offers less preferable meat compared to Clarias macrocephalus, its large size and rapid growth rate due to its favorable food conversion ratio, and its resistance to diseases and extreme environmental conditions e.g. low dissolved oxygen level of the water, made it popular among fish farmers. It also offers a possibility for high stocking density without affecting growth and productivity of the fish., This Special Problem was conducted to compare performance of triploid C. gariepinus x C. gariepinus cross exposed to cold shock from the normal diploid individuals, in terms of fertilization, hatching, and survival rates at day 2 and day 5 post-hatching. Cold shock treatments of the artificially fertilized eggs were done for 15 minutes duration at 5 degrees centigrade, 7 degrees centigrade, and 9 degrees centigrade. Experimental results revealed that the control group obtained higher fertilization and hatching rate values compared to the experimental group. Furthermore, it was observed that there was a lower survival rate in the cold-treated fish compared to the control treatment. This can be attributed to a variety of intrinsic and extrinsic factors, including quality of eggs used and pond water condition during the duration of the study. Development of abnormal fry was also observed. Among the cold shock treatments, 7 degrees centigrade obtained the highest survival rate.